Copepod parasite Lepeophtheirus kabatai (Ho & Dojiri, 1977) infestation in orange spotted grouper, Epinephelus coioides (Hamilton, 1822) and its control in captivity - Ranjan, Ritesh; Xavier, Biji; Santhosh, B.; Megarajan, Sekar; Ghosh, Shubhadeep (Indian Journal of Fisheries, 2018)
Parasitic infection in the orange spotted grouper Epinephelus coioides (Hamilton, 1822) and its control measures in captive conditions were studied. Wild collected groupers after 8 weeks of rearing in captivity showed lethargy and sluggishness. The caligid parasite, Lepeophtheirus kabatai (Ho & Dojiri, 1977) was identified from the affected fishes. This parasite was also prevalent in wild fish, however at lower prevalence (11%). The mean intensity of L. kabatai in fishes reared in captivity was 92.85Â±10.71, whereas in wild fish it was 3.54Â±1.61. Infected cultured fish were randomly assigned to one of five treatment groups (Group A, B, C, D and E). Group A fishes were given dip treatment in freshwater for 5 min, whereas groups B, C, D and E were given bath treatment in formalin @ 50, 100, 150 and 200 mg l-1 respectively for 30 min, followed by 5 min dip in freshwater. Group E fish were fully free of the infestation and no re-infestation was seen in them even after two months. This is the first study to confirm L. kabatai infestation in orange spotted grouper in both wild and cultured fish; and formalin treatment @ 200 mg l-1 was found effective control the infestation in captivity.